GEOMETRIK MASALALARNI BAJARISHNING ENG QULAY ALGORITMLARI - Rixsiboyev, U.T. (GOLDEN BRAIN, 2024)
This article is about the efficieucy of using algorithm & the ways of soling them with positional tasks.